Generalized window advertising for TCP congestion control - Mario Gerla; Renato Cigno; Saverio Mascolo; Wenjie Weng (European Transactions on Telecommunications, 2002)
Abstract Congestion in the Internet is a major cause of network performance degradation. The Generalized Window Advertising (GWA) scheme proposed in this paper is a new approach for enhancing the congestion control properties of TCP. GWA requires only minor modifications to the existing protocol stack and is completely backward compatible, allowing GWA-hosts to interact with non-GWA hosts without modifications. GWA exploits the notion of end-host-network cooperation, with the congestion level notified from the network to end hosts. It is based on solid control theory results mat guarantee performance and stable network operation. GWA is able to avoid window oscillations and the related fluctuations in offered load and network performance. This makes it more robust to sustained network overload due to a large number of connections competing for the same bottleneck, a situation where traditional TCP implementations fail to provide satisfactory performance. GWA-TCP is compared with traditional TCP, TCP with RED and also ECN using the ns-2 simulator. Results show that in most cases GWA-TCP outperforms the traditional schemes. In particular, when compared with ECN, it provides smoother network operation and increased fairness.